A productive exposition for the thermal post buckling problem of orthotropic circular plates by using relevant admissible function for lateral displacement - Anju V Nair; Abdul Rahman Mohd Kasim; Mohd Zuki Salleh (Annals of Mathematical Modeling, 2019)
A suitable mathematical formulation is used to study the thermal post buckling problem of orthotropic circular plates is presented herein. The total energy equation is reduced by assuming algebraic function for lateral displacement w. The radial tension per unit length is calculated by substituting the value of orthotropic parameter under simply supported and clamped boundary conditions. The thermal post buckling load carrying capacity of the plate is evaluated using integrated average for various values of orthotropic parameter β, and the numerical results obtained from the present investigation are compared with the results obtained from the known literatures. The results obtained for both cases are concurs well with reference values and the numerical results using integrated average shows more accurate values for the post buckling load.